TRAINING TO IMPROVE THE PHYSICAL CONDITION OF INDONESIA BADMINTON ELITE ATHLETES - Iwan Hermawan; Fahmy Fachrezzy; Shela Ginanjar; Dena Widyawan; Fachri Husaini; Rony Syaifullah (International Journal of Engagement and Empowerment, 2023)
The purpose of Community Service activities is one of the pillars of the Tri Dharma of Higher Education, in addition to the Dharma of Education and Teaching and the Dharma of Research. Community Service Research which is an integral part of the Tri Dharma of Higher Education which is inseparable from the other two dharmas involving the academic community including lecturers, students, education staff and alumni. This study aims to determine the Training for Indonesian Badminton Athletes in the context of Preparation for the 2023 International Championship. This study used a survey method. The samples in this study were Indonesian Badminton Pelatnas Athletes. The data analysis technique used in this study is using descriptive analysis. Research on Physical Condition Training of Indonesian Badminton Athletes so that athletes understand the importance of physical exercise, carry out physical training programs. All those involved in this training must get in-depth briefing in order to be able to carry out the training program appropriately according to the target or goal at the 2023 International Championship and achieve optimal achievements and where at the same time Indonesia can improve achievements in sports, especially Badminton. The target to be achieved is so that athletes can understand the elements of physical condition and how to improve it as one of the efforts to improve. The output to be achieved is that athletes understand about the elements of physical condition and how to improve it, especially badminton for Pelatnas Athletes at PBSI and the publication of scientific papers in national service journals. To achieve this, there are two methods used, the first is to make observations in the field and collaborate with partners. The second stage is to provide training on physical condition for Pelatnas Athletes at PBSI. The third stage evaluates the achievements achieved in the training activity